2011
DOI: 10.1074/jbc.m110.186338
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-independent Control of Peptide Conformation in Liposomal Vaccines for Targeting Protein Misfolding Diseases

Abstract: Synthetic peptide immunogens that mimic the conformation of a target epitope of pathological relevance offer the possibility to precisely control the immune response specificity. Here, we performed conformational analyses using a panel of peptides in order to investigate the key parameters controlling their conformation upon integration into liposomal bilayers. These revealed that the peptide lipidation pattern, the lipid anchor chain length, and the liposome surface charge all significantly alter peptide conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 50 publications
4
51
0
7
Order By: Relevance
“…An array of Aβ1-15 sequences are anchored to the surface of liposomes adopting an aggregated β-sheet structure that acts as conformational epitope. In preclinical studies, repeated subcutaneous injection of ACI-24 into AD transgenic mice generated high titers of anti-Aβ antibodies, decreasing the concentration of insoluble Aβ1-40 and Aβ1-42, and of soluble Aβ1-42 [72,73]. ACI-24 also improved novel object recognition without triggering proinflammatory responses [73].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…An array of Aβ1-15 sequences are anchored to the surface of liposomes adopting an aggregated β-sheet structure that acts as conformational epitope. In preclinical studies, repeated subcutaneous injection of ACI-24 into AD transgenic mice generated high titers of anti-Aβ antibodies, decreasing the concentration of insoluble Aβ1-40 and Aβ1-42, and of soluble Aβ1-42 [72,73]. ACI-24 also improved novel object recognition without triggering proinflammatory responses [73].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…The palmitoylated human ␤-amyloid (A␤, aa1-15) peptide adopts an aggregated ␤-sheet conformation on liposomes. 5 While previous reports have suggested that nonreplicating protein vaccines do not enable TI isotype switching, 6,7 the present study in mice demonstrates that switch is feasible with a correct structural assembly of antigen and adjuvant. This result could pave the way for vaccination of patients with T-cell deficiencies or elderly, or when T-cell involvement is associated with immunopathology or autoimmunity, for example, encephalitis in Alzheimer disease.…”
Section: Introductionmentioning
confidence: 66%
“…5,8 The liposomes were sterilized by filtration and endotoxin free. Each dose (200 L) contained 78 g of PalmA␤1-15 and 12 g of MPLA.…”
Section: Preparation Of Liposomesmentioning
confidence: 99%
“…The vaccine contains 16 copies of a synthetic tau fragment that is phosphorylated at the protein's pathological phosphorylation residues S396 and S404 and is anchored into a lipid bilayer. It uses the adjuvant MPLA (104). In pre-clinical studies it rapidly generated high titers of polyclonal IgG antibodies specifically directed against phosphorylated tau, rather than non-phosphorylated tau, reducing soluble tau as well as insoluble, aggregated tau in brain extracts (105).…”
Section: Chf-5074mentioning
confidence: 99%